Investigating the Factors Influencing the Rejection of Cognitive Performance Tests in the Banking Sector of Pakistan - Faraz Ali Memon; Uzair Inayat Memon (Business Review)
This study explored the barriers hindering the adoption of cognitive performance tests in HR practices within Pakistan’s banking sector and developed practical recommendations for enhancing their implementation. A qualitative approach was adopted, and 16 semi-structured interviews were conducted with HR professionals from major banks in large cities. It aims to explore potential barriers to using and incorporating cognitive ability tests in selection practices. The data was later interpreted, and the findings highlighted five key themes. The results revealed factors influencing the rejection of cognitive performance tests in Pakistan’s banking sector. It includes cultural factors such as senior management resistance and emphasis on conventional HRM practices. The interviewed HR professionals highlighted the absence of structures and policies to implement cognitive testing in the selection process. Data protection problems, liabilities and concerns about how the test results would be used were also behind the reluctance. The study identifies awareness and education on using cognitive testing as an area that deserves more attention and has to be developed. The banking sector in Pakistan may benefit from using cognitive testing for selection and performance improvement.